Self-Study with the Educational Technology Tell Me More: What EFL Learners do - George Gyamfi; Panida Sukseemuang; Kornsak Tantiwich; Pittayatorn Kaewkong (Open Praxis, 2019)
This study investigated 350 English as a foreign language (EFL) undergraduate students’ use of Tell Me More (TMM), a language learning technology, for self-study in a university in the south of Thailand. Two questions guided the study: 1) What were learners’ self-study practices with the TMM program? 2) How did learners’ self-study practices enhance or undermine the purpose of using the TMM program? Self-report questionnaire with subscales from Students Approaches to Learning and a semi-structured focused group interview were used to investigate the participants’ practices, effort and persistence on the TMM. The findings indicated that the learners multitasked to compensate for the lack of support from instructors and for assessment purposes, sometimes left the program on to count the time. The findings on the time of use suggested that self-study practices do not depend only on learners’ attitude or features of the learning environment but also goals set by instructors. Additionally, the findings showed that learners made moderate effort of use and were inconsistent in their self-study practices. The findings shed new light on what accounts for the effective use of educational technologies and how practices could be improved. This study would guide developers of online learning curriculums and educators on learning goals and assessment types to be incorporated in online self-study programs.